Basalt fiber reinforced concrete for high stress area of composite beam of cable-stayed bridge and construction method thereof
Patent Information
- Application Number
- CN202611083728.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]上述公开的这种斜拉桥在混凝土中掺入钢纤维提升抗裂性能,但钢纤维密度大,搅拌时易沉淀结团,与混凝土浆体结合性差,且易产生电化学腐蚀,影响钢筋结构安全性;同时钢纤维对搅拌、振捣设备磨损大,施工工艺要求高
[0029] Compared to existing technologies, applying basalt fiber concrete to the anchorage zone of the top plate of the main girder of a large cable-stayed bridge and the wet joint of the precast bridge deck utilizes the high tensile strength and high elastic modulus of basalt fibers, combined with the shrinkage compensation function of micro-expansion concrete, to achieve the dual effects of crack prevention (compensating shrinkage to offset tensile stress) and crack resistance (fiber bridging to inhibit crack propagation). This effectively avoids structural cracks in the high-stress zone of the top plate of the main girder and the wet joint during the tensioning of the cable stays and under operating conditions, thereby improving the crack resistance and toughness of the structure.
Smart Images

Figure CN122916541A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable-stayed bridge construction technology, specifically to a basalt fiber reinforced concrete for the high-stress zone of composite beams in cable-stayed bridges and its construction method. Background Technology
[0002] The cable anchorage zone of the main girder side beam of a large cable-stayed bridge is a typical high-stress area. During the tensioning of the cable stays and under the operating conditions of the bridge, this area will bear huge tensile and shear stresses. At the same time, the cast-in-place wet joint between the precast bridge decks is a key structure for the overall connection of the bridge decks. Due to the inconsistent shrinkage of the old and new concrete and the repeated action of prestressing tension and vehicle loads, structural cracks are very likely to occur.
[0003] In existing technologies, ordinary C60 micro-expansion concrete is often used for the construction of high-stress areas and wet joints of composite beams in large cable-stayed bridges. Ordinary concrete is brittle, has poor crack resistance, and slow early strength development. To ensure the stability of the concrete structure during cable tensioning, the concrete curing period must be set to 7 days. Tensioning can only be carried out after the strength and elastic modulus reach more than 95% of the design value. This results in a long construction cycle for the main beam and makes it difficult to advance the overall bridge closure period. Moreover, during long-term operation, ordinary concrete is prone to the appearance of micro-cracks in high-stress areas, which gradually expand, reducing structural durability and affecting the overall service life of the bridge.
[0004] Chinese patent CN103898834A discloses a steel-concrete composite beam and truss-type cable-stayed bridge and its construction method, including a pylon, a beam body fixed to the pylon, cables connecting the pylon and the beam body, and a bridge deck panel set on the beam body. The bridge deck panel includes a bottom plate and a top plate. The bottom plate is a steel plate set on the beam body, and the top plate is a high crack-resistant steel fiber reinforced concrete panel cast on the bottom plate. The top plate and the bottom plate are connected as a whole by shear keys.
[0005] The aforementioned cable-stayed bridge incorporates steel fibers into the concrete to improve its crack resistance. However, the high density of steel fibers makes them prone to sedimentation and clumping during mixing, resulting in poor bonding with the concrete slurry and easy electrochemical corrosion, which affects the safety of the steel reinforcement structure. At the same time, steel fibers cause significant wear on mixing and vibration equipment, and the construction process requires high precision. Summary of the Invention
[0006] The present invention aims to overcome the defects in the prior art and provide a basalt fiber concrete for high stress zones of composite beams in cable-stayed bridges, which has good crack resistance, rapid early strength development, and short main beam construction period, as well as its construction method.
[0007] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: a basalt fiber concrete for the high stress zone of composite beams in cable-stayed bridges, comprising gel material, aggregate, water, water-reducing agent and basalt fiber;
[0008] For every cubic meter of concrete, the amount of gel material added is 400-600 kg, the amount of aggregate is 1650-1900 kg, the amount of water-reducing agent is 6.5-7 kg, the amount of basalt fiber is 10-20 kg, and the water-cement ratio is 0.25-0.35.
[0009] The gel material includes cement, carbon ash, slag powder, and an expanding agent;
[0010] The aggregates include crushed stone and natural sand.
[0011] As a preferred embodiment of the present invention, the amount of gel material added per cubic meter of concrete is 500 kg, the amount of aggregate is 1775 kg, the amount of water-reducing agent is 6.75 kg, the amount of basalt fiber is 15 kg, and the water-cement ratio is 0.29.
[0012] As a preferred embodiment of the present invention, the gel material comprises 340 kg of cement, 65 kg of carbon ash, 45 kg of slag powder and 50 kg of expansion agent per cubic meter of concrete.
[0013] As a preferred embodiment of the present invention, each cubic meter of concrete comprises 1083 kg of crushed stone and 692 kg of natural sand.
[0014] As a preferred embodiment of the present invention, the concrete contains 145 kg of water per cubic meter.
[0015] As a preferred embodiment of the present invention, the performance indicators of the basalt fiber are as follows: fiber length 33-37mm, single fiber diameter 0.6-1.0mm, tensile strength ≥1000MPa, density 1.9-2.1g / cm³, elastic modulus ≥45GPa, elongation at break ≥2.0%, aspect ratio controlled at 45-60, and alkali resistance strength retention rate ≥65%.
[0016] A construction method for basalt fiber reinforced concrete in the high-stress zone of composite beams in cable-stayed bridges, based on basalt fiber reinforced concrete for the high-stress zone of composite beams in cable-stayed bridges, includes the following steps:
[0017] Step S1: Prepare raw materials. Prepare the raw materials for basalt fiber concrete according to the mix proportion.
[0018] Step S2: Prepare basalt fiber concrete using a "dry mixing + wet mixing" process. First, dry mix the gel material, aggregate, and basalt fiber for 2-3 minutes, then add water and water-reducing agent and wet mix for 3-4 minutes until the basalt fiber is evenly dispersed and free of lumps.
[0019] Step S3: Define the high-stress zone of the composite beam of the cable-stayed bridge, including the anchorage zone of the top plate of the main beam at the edge of the composite beam and the wet joint of the precast bridge deck.
[0020] Step S4: Basalt fiber concrete pouring. The basalt fiber concrete is poured into the anchorage area of the top plate of the main beam at the edge of the composite beam. The mixed basalt fiber concrete is transported to the anchorage area of the top plate of the main beam at the edge of the composite beam. The concrete is vibrated in layers with an immersion vibrator. Each layer is no more than 300mm thick. The concrete is vibrated until the surface of the concrete is covered with slurry and there are no air bubbles. This ensures that the concrete in the anchorage area of the top plate of the main beam at the edge of the composite beam is dense and formed, and avoids the formation of internal pores due to insufficient vibration.
[0021] Step S5: Basalt fiber concrete pouring, precast bridge deck wet joint pouring. After the composite beam side main beam construction in step S4 is completed, the precast bridge deck is hoisted, the wet joint reinforcement is tied, the prestressed duct is installed, and then basalt fiber concrete is poured. The pouring length is 24-28m at a time. After vibration, the concrete surface is smoothed and roughened to enhance the bonding force with the subsequent pavement layer.
[0022] Step S6: Thermal insulation and moisture retention curing. Immediately after the basalt fiber concrete is poured, it is covered with a film to retain moisture, and then covered with an outer layer of thermal insulation cotton quilt for thermal insulation curing. Temperature sensors are pre-embedded inside the basalt fiber concrete and are respectively placed at the bottom main reinforcement, between the two layers of main reinforcement, and at the top main reinforcement to monitor the concrete temperature at different depths in real time, ensuring that the internal temperature and the ambient temperature do not exceed 25℃ and the curing age is not less than 5 days.
[0023] Step S7: Strength testing. After curing for 5 days, test the compressive strength and compressive modulus of elasticity of the basalt fiber concrete. After confirming that both have reached more than 95% of the design value, carry out the secondary tensioning operation of the cable stays.
[0024] Step S8: Post-construction maintenance. After the stay cables are tensioned, continue to keep the basalt fiber concrete moist for curing. The total curing period shall not be less than 14 days.
[0025] Step S9: First piece construction. Before construction, a first piece test is conducted. After the first piece acceptance summary is completed and all performance standards are met, batch construction can proceed.
[0026] In a preferred embodiment of the present invention, the basalt fiber in step S2 is fed by manual spreading and is fed into the mixing pot simultaneously with the aggregate.
[0027] As a preferred embodiment of the present invention, the slump of the basalt fiber concrete in step S2 is 190-210 mm and the spread is ≥500 mm.
[0028] As a preferred embodiment of the present invention, in step S7, the basalt fiber concrete strength test requires the basalt fiber concrete to have a compressive strength ≥70MPa, a compressive elastic modulus ≥41000MPa, and a splitting tensile strength ≥5.2MPa.
[0029] Compared to existing technologies, applying basalt fiber concrete to the anchorage zone of the top plate of the main girder of a large cable-stayed bridge and the wet joint of the precast bridge deck utilizes the high tensile strength and high elastic modulus of basalt fibers, combined with the shrinkage compensation function of micro-expansion concrete, to achieve the dual effects of crack prevention (compensating shrinkage to offset tensile stress) and crack resistance (fiber bridging to inhibit crack propagation). This effectively avoids structural cracks in the high-stress zone of the top plate of the main girder and the wet joint during the tensioning of the cable stays and under operating conditions, thereby improving the crack resistance and toughness of the structure.
[0030] Under the action of basalt fiber concrete with a specific mix ratio, the basalt fiber concrete can achieve good workability, uniform dispersion of basalt fibers, and a compressive strength of ≥70MPa after 5 days of standard curing and ≥72MPa after 5 days of curing under the same conditions. Both reach more than 95% of the design strength and elastic modulus, meet the strength requirements for secondary tensioning of cable stays, shorten the concrete curing period from the traditional 7 days to 5 days, shorten the construction cycle of a single beam segment by 2 days, significantly reduce the construction period of the main beam of the cable-stayed bridge, and achieve the early closure of the main bridge.
[0031] Basalt fiber has a density of 1.9-2.1 g / cm³, which is only one-quarter of that of ordinary steel fiber. Its density is close to that of concrete slurry. There is no sedimentation or clumping during mixing, and it does not cause wear on mixing and vibration equipment. The construction process is simple. At the same time, basalt fiber has good corrosion resistance, is non-magnetic, and does not generate potential difference, which can avoid electrochemical corrosion of steel bars. Its coefficient of thermal expansion is consistent with that of concrete, and it will not generate additional stress when the temperature changes, which significantly improves the durability and service life of bridge structures.
[0032] The "dry mixing + wet mixing" mixing process ensures that the basalt fiber is evenly dispersed, the layered vibration ensures that the concrete is dense and formed, the thermal insulation and moisture retention curing process of film and thermal insulation cotton blanket promotes the early strength development of concrete, and the pre-embedded temperature sensor monitors the temperature in real time to avoid temperature cracks. The first piece construction guidance system ensures that the construction quality is controllable, and the various process steps are smoothly connected, which is suitable for the on-site construction conditions of large cable-stayed bridges.
[0033] The overall stress system of the composite beam edge main beam top plate anchorage zone and the wet joint of the precast bridge deck, the high tensile strength and high toughness of basalt fiber concrete can effectively disperse the stress concentration in the high stress zone and improve the overall stress performance of the structure. At the same time, the concrete has stable strength development in the later stage, and the compressive strength after 28 days of standard curing is ≥96MPa, which is far higher than the design requirements, providing a solid guarantee for the long-term safe operation of the bridge.
[0034] Compared to steel fiber reinforced concrete, it has no risk of corrosion, less equipment wear, and lower maintenance costs. It combines advanced technology with economic rationality and can be widely used in the construction of high-stress areas and wet joints of composite beams in various large cable-stayed bridges and suspension bridges. Attached Figure Description
[0035] Figure 1 This is a schematic diagram showing the location of the high-stress zone in the composite beam of a cable-stayed bridge;
[0036] Figure 2 This is a schematic diagram of the pouring of wet joints in precast bridge decks;
[0037] Figure 3 This is a schematic diagram of the maintenance of wet joints in precast bridge decks;
[0038] Figure label: 1. Anchorage zone of top plate of main beam on edge of composite beam; 2. Wet joint of precast bridge deck. Detailed Implementation
[0039] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0040] like Figure 1-3 As shown, a basalt fiber concrete for the high-stress zone of composite beams in cable-stayed bridges includes a gel material, aggregate, water, water-reducing agent, and basalt fiber.
[0041] The high-stress zone of the composite beam of the cable-stayed bridge includes the anchorage zone 1 of the top plate of the main beam on the side of the composite beam and the cast-in-place wet joint 2 between the precast bridge decks. In actual use, the cast-in-place wet joint 2 between the precast bridge decks has a maximum width of 2.6m, a maximum depth of 0.61m, and a single pouring length of 24-28m. It forms an integral load-bearing structure with the anchorage zone 1 of the top plate of the main beam on the side of the composite beam, ensuring effective force transmission and avoiding local stress concentration.
[0042] For every cubic meter of concrete, the amount of gel material added is 400-600 kg, the amount of aggregate is 1650-1900 kg, the amount of water-reducing agent is 6.5-7 kg, the amount of basalt fiber is 10-20 kg, and the water-cement ratio is 0.25-0.35.
[0043] The gel material includes cement, carbon ash, slag powder, and an expanding agent.
[0044] The aggregates include crushed stone and natural sand, with the crushed stone being 5-20mm in size.
[0045] For every cubic meter of concrete, the amount of gel material added is 500 kg, the amount of aggregate is 1775 kg, the amount of water-reducing agent is 6.75 kg, the amount of basalt fiber is 15 kg, the water-cement ratio is 0.29, the water-reducing agent is polycarboxylate high-efficiency water-reducing agent, and the basalt fiber is short-cut basalt fiber.
[0046] The gel material comprises 340 kg of cement, 65 kg of carbon ash, 45 kg of slag powder and 50 kg of expansion agent per cubic meter of concrete.
[0047] The cement used is Type II Portland cement with a compressive strength ≥52.5MPa. The fly ash used is Grade I fly ash with a fineness ≤12%, loss on ignition ≤5.0%, and water requirement ≤95%. The slag powder used is S95 granulated blast furnace slag powder with a 28-day activity index ≥95%. The gel material is a compound of cement, fly ash, slag powder, and expansion agent.
[0048] Each cubic meter of concrete contains 1083 kg of crushed stone and 692 kg of natural sand.
[0049] The amount of water included is 145 kg per cubic meter of concrete.
[0050] Basalt fiber reinforced concrete can actively compensate for shrinkage and offset tensile stress during the mixing process to prevent cracking. Basalt fibers bridge cracks after they appear to inhibit their propagation and achieve crack resistance. The combination of the two forms a crack-resistant system that combines prevention and resistance.
[0051] During the mixing process, basalt fiber reinforced concrete generates expansive crystals such as ettringite and calcium hydroxide under the action of the expansive agent. This results in controllable micro-expansion throughout the hardening process of the concrete. This micro-expansion can offset the plastic shrinkage caused by cement hydration and water evaporation, avoid surface plastic cracks, and also compensate for the self-shrinkage and drying shrinkage caused by the hydration of cementitious materials.
[0052] Basalt fibers can form a continuous three-dimensional skeleton in the concrete matrix. When local stress concentration occurs in the concrete matrix and microcracks inevitably form, basalt fibers will bear the tensile stress that was originally borne by the concrete, firmly binding the matrix on both sides of the crack. At the same time, basalt fibers share the tensile stress, greatly reducing stress concentration at the crack tip, preventing microcracks from connecting and developing into through-cracks that are harmful. They break down a single wide crack into a large number of harmless microcracks, improving the ductility and ultimate tensile deformation capacity of the concrete.
[0053] The performance indicators of basalt fiber are as follows: fiber length 33-37mm, single fiber diameter 0.6-1.0mm, tensile strength ≥1000MPa, density 1.9-2.1g / cm³, elastic modulus ≥45GPa, elongation at break ≥2.0%, aspect ratio controlled at 45-60, and alkali resistance strength retention rate ≥65%.
[0054] The performance indicators of basalt fiber are close to the density of concrete paste. Basalt fiber is easy to disperse evenly during the mixing process with concrete paste and is not easy to clump. Moreover, the thermal expansion coefficient of basalt fiber is consistent with that of concrete paste, so no additional stress will be generated when the temperature changes, thus avoiding cracks.
[0055] A construction method for basalt fiber reinforced concrete in the high-stress zone of composite beams in cable-stayed bridges, based on basalt fiber reinforced concrete for the high-stress zone of composite beams in cable-stayed bridges, includes the following steps:
[0056] Step S1: Prepare raw materials. Prepare the raw materials for basalt fiber concrete according to the mix proportion.
[0057] Step S2: Prepare basalt fiber concrete using a "dry mixing + wet mixing" process. First, dry mix the gel material, aggregate, and basalt fiber for 2-3 minutes, then add water and water-reducing agent and wet mix for 3-4 minutes until the basalt fiber is evenly dispersed and free of lumps.
[0058] Basalt fiber is fed by manual spreading and is simultaneously fed into the mixing pot along with the aggregate to ensure that the basalt fiber and aggregate are delivered synchronously in each batch, thus avoiding clumping of the basalt fiber. The slump of the basalt fiber concrete is 190-210mm and the spread is ≥500mm.
[0059] Step S3: Define the high-stress zone of the composite beam of the cable-stayed bridge, including the anchorage zone 1 of the top plate of the main beam on the side of the composite beam and the wet joint 2 of the precast bridge deck. The maximum width of the cast-in-place wet joint 2 between the precast bridge decks is 2.6m and the maximum depth is 0.61m in actual use. The single pouring length is 24-28m. It forms an integral load-bearing structure with the anchorage zone 1 of the top plate of the main beam on the side of the composite beam to ensure effective force transmission and avoid local stress concentration.
[0060] Step S4: Basalt fiber concrete pouring. The basalt fiber concrete is poured into the anchorage zone 1 of the top plate of the main beam of the composite beam. The mixed basalt fiber concrete is transported to the anchorage zone 1 of the top plate of the main beam of the composite beam and vibrated in layers using an immersion vibrator. Each layer is no more than 300mm thick. Vibration is continued until the concrete surface is smooth and free of air bubbles, ensuring that the concrete in the anchorage zone 1 of the top plate of the main beam of the composite beam is dense and compacted. This avoids internal voids caused by insufficient compaction. After vibration, the surface is smoothed and roughened to ensure that it forms an integral whole with the bridge deck.
[0061] Step S5: Basalt fiber concrete pouring, precast bridge deck wet joint 2 pouring. After the composite beam side main beam construction in step S4 is completed, the precast bridge deck is hoisted, the wet joint reinforcement is tied, the prestressed duct is installed, and then basalt fiber concrete is poured. The pouring length is 24-28m in one go. After vibration, the concrete surface is smoothed and roughened to enhance the bonding force with the subsequent pavement layer.
[0062] Step S6: Thermal Insulation and Moisture Curing. Immediately after the basalt fiber concrete is poured, it is covered with a film to retain moisture, and then covered with an outer layer of thermal insulation cotton quilt for thermal insulation curing. Temperature sensors are pre-embedded inside the basalt fiber concrete and are respectively placed at the bottom main reinforcement, between the two layers of main reinforcement, and at the top main reinforcement to monitor the concrete temperature at different depths in real time, ensuring that the internal temperature and the ambient temperature do not exceed 25℃, and the curing age is not less than 5 days. Thermal insulation curing can promote the full hydration reaction of concrete and improve the early strength development speed.
[0063] Step S7: Strength testing. After curing for 5 days, test the compressive strength and compressive modulus of elasticity of the basalt fiber concrete. After confirming that both have reached more than 95% of the design value, carry out the secondary tensioning operation of the cable stays. Compared with the traditional 7-day curing period, the construction cycle of a single beam segment is shortened by 2 days.
[0064] In the strength testing of basalt fiber reinforced concrete, the compressive strength must be ≥70MPa, the compressive elastic modulus must be ≥41000MPa, and the splitting tensile strength must be ≥5.2MPa.
[0065] Step S8: Post-construction maintenance. After the stay cables are tensioned, the basalt fiber concrete is kept moist and maintained for a total curing period of not less than 14 days to ensure that the concrete performance continues to improve and further enhance the structural durability.
[0066] Step S9: First piece construction. Before construction, a first piece test is conducted. After the first piece acceptance summary is completed and all performance standards are met, batch construction can proceed.
[0067] In practical application, this application was used in the construction of the anchorage zone 1 of the top plate of the composite beam of the main beam on the cross-port area and the Yongjiang Grand Bridge (a three-tower double-cable-stayed steel-concrete composite beam bridge with a span arrangement of 50+275+540+570+214+81m and a total length of 1730m) and the wet joint 2 of the precast bridge deck. The total volume of concrete for the wet joint of the whole bridge is about 5597.49m³, the maximum width of the wet joint is 2.6m, the maximum depth is 0.61m, and the length of a single pour is 24-28m.
[0068] Basalt fiber concrete was used for pouring. The basalt fiber was structurally reinforced short-cut basalt, with a dosage of 15 kg / m³. The fiber performance indicators were: length 35 mm, single fiber diameter 0.8 mm, tensile strength 1100 MPa, density 2.0 g / cm³, elastic modulus 48 GPa, elongation at break 2.2%, aspect ratio 50, and alkali resistance strength retention rate 70%. The basalt fiber concrete was a micro-expansion and shrinkage-compensating concrete with a water-cement ratio of 0.29. The mix proportions were: cement 340 kg / m³, fly ash 65 kg / m³, slag powder 45 kg / m³, expansion agent 50 kg / m³, natural sand 692 kg / m³, 5-20 mm crushed stone 1083 kg / m³, water 145 kg / m³, and polycarboxylate superplasticizer 6.75 kg / m³.
[0069] The process employs a "dry mixing + wet mixing" method. First, the cementitious materials, aggregates, and basalt fibers are dry mixed for 2.5 minutes, then water and water-reducing agent are added and wet mixed for 3.5 minutes. The fibers are manually spread to ensure uniform dispersion. The slump at the outlet is 200 mm, the spread is 540 mm, and the workability is good.
[0070] In the anchorage zone 1 of the top slab of the composite beam side main beam, the layered vibration is carried out using an immersion vibrator, with each layer being 250mm thick. The cast-in-place wet joint 4 is poured in one go for 26m. After vibration, the surface is smoothed and roughened to ensure that it forms an integral whole with the bridge deck.
[0071] Immediately after pouring, cover with a film and insulation blanket, and pre-embed temperature sensors inside the concrete (one each in the bottom, middle, and top layers) to monitor the temperature in real time. During curing, the highest internal temperature is 35.8℃, and the temperature difference with the atmosphere is ≤20℃.
[0072] After curing for 5 days, the compressive strength of the test blocks cured under the same conditions was 72.6 MPa and the compressive elastic modulus was 41600 MPa, while the compressive strength of the test blocks cured under standard conditions was 71.8 MPa and the splitting tensile strength was 5.22 MPa, all of which reached more than 95% of the design values.
[0073] After the strength test was completed, the second tensioning operation of the cable was carried out. No cracks were generated in the high stress area and wet joint during the tensioning process.
[0074] The concrete curing period was shortened from 7 days to 5 days. With 12 construction cycles of beam segments, the construction period was shortened by 24 days each time. The main bridge was closed ahead of schedule, avoiding the construction risks of the long cantilever abutment of the main beam. During the tensioning of the stay cables and subsequent operation, no structural cracks appeared in the high stress zone of the main beam anchorage and wet joints of the composite beam. The concrete compressive strength after 28 days of standard curing was 96.0 MPa, which is far higher than the design requirements. The basalt fiber was evenly dispersed during construction, causing no wear on the equipment. Compared with steel fiber concrete, there is no risk of corrosion in the later stage, which greatly improves the durability of the bridge structure.
[0075] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention; therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
[0076] Although this document frequently uses reference numerals such as "anchorage zone 1 of the top plate of the main beam at the edge of the composite beam" and "wet joint of the precast bridge deck 2," the possibility of using other terms is not excluded. These terms are used merely for the convenience of describing and explaining the essence of the invention; interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A basalt fiber reinforced concrete for high-stress zones in composite beams of cable-stayed bridges, characterized in that, Includes gelling materials, aggregates, water, water-reducing agents, and basalt fibers; For every cubic meter of concrete, the amount of gel material added is 400-600 kg, the amount of aggregate is 1650-1900 kg, the amount of water-reducing agent is 6.5-7 kg, the amount of basalt fiber is 10-20 kg, and the water-cement ratio is 0.25-0.
35. The gel material includes cement, carbon ash, slag powder, and an expanding agent; The aggregates include crushed stone and natural sand.
2. The basalt fiber reinforced concrete for high-stress zones of composite beams in cable-stayed bridges according to claim 1, characterized in that, Based on one cubic meter of concrete, the amount of gel material added is 500 kg, the amount of aggregate is 1775 kg, the amount of water-reducing agent is 6.75 kg, the amount of basalt fiber is 15 kg, and the water-cement ratio is 0.
29.
3. The basalt fiber reinforced concrete for high-stress zones of composite beams in cable-stayed bridges according to claim 2, characterized in that, The gel material comprises 340 kg of cement, 65 kg of carbon ash, 45 kg of slag powder and 50 kg of expansion agent per cubic meter of concrete.
4. The basalt fiber reinforced concrete for high-stress zones of composite beams in cable-stayed bridges according to claim 2, characterized in that, Each cubic meter of concrete contains 1083 kg of crushed stone and 692 kg of natural sand.
5. The basalt fiber reinforced concrete for high-stress zones of composite beams in cable-stayed bridges according to claim 2, characterized in that, The amount of water included is 145 kg per cubic meter of concrete.
6. The basalt fiber reinforced concrete for high-stress zones of composite beams in cable-stayed bridges according to claim 1, characterized in that, The performance indicators of the basalt fiber are as follows: fiber length 33-37mm, single fiber diameter 0.6-1.0mm, tensile strength ≥1000MPa, density 1.9-2.1g / cm³, elastic modulus ≥45GPa, elongation at break ≥2.0%, aspect ratio controlled at 45-60, and alkali resistance strength retention rate ≥65%.
7. A construction method for basalt fiber reinforced concrete in the high-stress zone of composite beams in cable-stayed bridges, based on the basalt fiber reinforced concrete for the high-stress zone of composite beams in cable-stayed bridges as described in any one of claims 1-6, characterized in that, Includes the following steps: Step S1: Prepare raw materials. Prepare the raw materials for basalt fiber concrete according to the mix proportion. Step S2: Prepare basalt fiber concrete using a "dry mixing + wet mixing" process. First, dry mix the gel material, aggregate, and basalt fiber for 2-3 minutes, then add water and water-reducing agent and wet mix for 3-4 minutes until the basalt fiber is evenly dispersed and free of lumps. Step S3: Define the high stress zone of the composite beam of the cable-stayed bridge, including the anchorage zone of the top plate of the main beam side of the composite beam (1) and the wet joint of the precast bridge deck (2). Step S4: Basalt fiber concrete pouring. The basalt fiber concrete is poured into the anchorage area (1) of the top plate of the main beam of the composite beam. The mixed basalt fiber concrete is transported to the anchorage area (1) of the top plate of the main beam of the composite beam. The immersion vibrator is used to vibrate in layers, with each layer not exceeding 300mm in thickness. Vibrate until the concrete surface is covered with slurry and there are no air bubbles, to ensure that the concrete in the anchorage area (1) of the top plate of the main beam of the composite beam is dense and formed, and to avoid internal pores caused by insufficient vibration. Step S5: Basalt fiber concrete pouring, precast bridge deck wet joint (2) pouring. After the composite beam side main beam in step S4 is completed, the precast bridge deck is hoisted, the wet joint reinforcement is tied, the prestressed pipe is installed, and then basalt fiber concrete is poured. The pouring length is 24-28m at a time. After vibration, the concrete surface is smoothed and roughened to enhance the bonding force with the subsequent pavement layer. Step S6: Thermal insulation and moisture retention curing. Immediately after the basalt fiber concrete is poured, it is covered with a film to retain moisture, and then covered with an outer layer of thermal insulation cotton quilt for thermal insulation curing. Temperature sensors are pre-embedded inside the basalt fiber concrete and are respectively placed at the bottom main reinforcement, between the two layers of main reinforcement, and at the top main reinforcement to monitor the concrete temperature at different depths in real time, ensuring that the internal temperature and the ambient temperature do not exceed 25℃ and the curing age is not less than 5 days. Step S7: Strength test. After curing for 5 days, test the compressive strength and compressive modulus of elasticity of the basalt fiber concrete. After confirming that both have reached more than 95% of the design value, carry out the secondary tensioning operation of the cable stay. Step S8: Post-construction maintenance. After the stay cables are tensioned, continue to keep the basalt fiber concrete moist for curing. The total curing period shall not be less than 14 days. Step S9: First piece construction. Before construction, a first piece test is conducted. After the first piece acceptance summary is completed and all performance standards are met, batch construction can proceed.
8. A construction method for basalt fiber reinforced concrete in the high-stress zone of composite beams in cable-stayed bridges according to claim 7, characterized in that, In step S2, basalt fiber is fed by manual spreading and is fed into the mixing pot simultaneously with the aggregate.
9. A construction method for basalt fiber reinforced concrete in the high-stress zone of composite beams in cable-stayed bridges according to claim 7, characterized in that, In step S2, the slump of the basalt fiber concrete leaving the mixer is 190-210 mm, and the spread is ≥500 mm.
10. A construction method for basalt fiber reinforced concrete in the high-stress zone of composite beams in cable-stayed bridges according to claim 7, characterized in that, In step S7, the basalt fiber reinforced concrete strength test requires a compressive strength ≥70MPa, a compressive elastic modulus ≥41000MPa, and a splitting tensile strength ≥5.2MPa.
Citation Information
Patent Citations
Concrete-filled steel tube composite beam and trussed cable tower cable-stayed bridge and construction method thereof
CN103898834A